Acumulação de competências tecnológicas e suas implicações para performance operacional: análise comparativa de duas empresas do grupo Lupatec em Caxias do Sul - RS - Denicol, Elias Milton (2001)
This work focuses on the implications of accumulation of technological competences for improvement of operational performance indicators. This relationship is examined in two mechanical industry firms in Caxias do Sul-RS, in the period 1985-2000. Based on a comparative case study, this work finds its ground in both qualitative and quantitative empirical evidences, collected in different sources in the firms, which are being studied. The examination of accumulation of technological competences is done through a structure of analysis existing in literature, which is specifically adapted to the mechanical industry. The examination of performance improvement is based on a set of typical operational indicators pertaining to mechanical industry. Studies of this nature are already found, mainly in Latin American literature, since the eighties. But, the application of these analytic structures in industrializing firms in Brazil is found only in the nineties. This work shows that within a unique enterprise group there is a different accumulation of technological competences, and it demonstrates that this process is not automatic. Moreover, it contributes to explain not only the differences between both firms, in terms of operational performance at some points in time, but also, how both firms got to (or did not get to) improve their performance indicators along time. This conclusion is not different from that of previous studies, but it derives from a study made in a specific industry (mechanical), which has not yet been studied in the south of Brazil.